Erosividade, coeficiente de chuva, padrões e período de retorno das chuvas de Quaraí e Rio Grande, RS - Bazzano, Marcos Gabriel Peñalva (2005)
The rainfall specifics characteristics vary from one region to another. The knowledge of the rainfall potential to cause erosion is necessary to plan agricultural and civil engineering activities. For Quarai and Rio Grande (RS, Brazil), were determined the rainfall erosivity and its relationship with precipitation and rainfall coefficient, rainfall patterns and rainfall return period. Were used rainfall data charts of 38 years of Quarai (1966-2003) and 23 years of Rio Grande (1957, 1959-1978 e 1980-1981). For each erosive rainfall were separated the segments of the rainfall chart with the same intensity and the data registered in worksheet. With the software Chuveros were estimated the mean monthly and annual rainfall erosivity, the EI30 index in the International System of Units and the rainfall patterns. The mean monthly values of precipitation and erosivity index were expressed as percentages of the mean annual values of precipitation and erosivity index, respectively, to obtain the curve of accumulated distribution of precipitation and erosivity index in function of time. The rainfall coefficient (Rc) was calculated. Were performed Pearson correlations and linear regressions between the erosivity index EI30 and the mean annual values of precipitation and rainfall coefficient.. The rainfall return period were calculated for 2, 5, 10, 20, 50 e 100 years. The mean annual values of EI30 for Quarai and Rio Grande were 9292.1 e 5135.0 MJ mm ha-1 h-1 ano-1, respectively. Were obtained the equations EI30 = -754.37 + 13.50 p (r2 = 0.85) e EI30 = - 47.35 + 82.72 Rc (r2 = 0.84) for Quarai. For Rio Grande the equations were not significant. In relation to the total of the rainfalls studied for each place, 44.3% of the number and 90.4% of the volume were erosive in Quarai, and 32.6% of the number and 99.3% of the volume were erosive in Rio Grande. The method of extreme distribution type I was adequate for obtaining the curves of intensity-duration-frequency. The rainfall return periods may be calculated by the equations using the values of the parameters found, or by the figures of intensity-durationfrequency.